The Influence of Return On Asset, Financial Leverage, and Company Size To Underpricing at Companies That Make Initial Public Offering (IPO) at Indonesia Stock Exchange. - Putu Widhiastina; Rida Prihatni (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
This study aimed to determine the influence of The Influence of return on asset, financial leverage, and size of company on underpricing. Underpricing is measured by division the difference between clossing prices and offering price with offering price, return on asset is measured by division net profit with total asset, financial leverage is measured by division total debt with total equity and size of company is mesured with total sales in annual report company. This study took a sample of initial public offering company listed in Indonesia Stock Exchange during the years 2010-2013. The data obtained by purposive sampling techniques and using multiple regression analysis. Simultaneous hypothesis testing result show that return on asset, financial leverage and company size simultaneously affect the underpricing. The partial hypothesis test result show that retun on asset, financial leverage and company size have a significant affect the underpricing. Keywords: Return On Assets, Financial Leverage, Company Size, Underpricing